FINANCE AND BALANCED GROWTH. (28th March 2013) - Trew, Alex
<x content-type="archive" xml:space="preserve">Abstract</x> We study the relationships between various concepts of financial development and balanced economic growth. A model of endogenous growth that incorporates roles for both financial efficiency and access to financial services permits a better understanding of the relationship between the size of the financial sector (value added) and growth. Higher financial value added results from some, but not all, kinds of finance-driven growth. If greater access rather than greater efficiency generates higher growth, then value added and growth can be positively correlated. We present some preliminary empirical results that support the importance of access alongside efficiency in explaining cross-country variations in growth.